Exclusive economic zone : state claims and the LOS Convention. - NADELSON, Robert (1992)
Examines the areas of contention between state practice and the LOS Convention. Concludes that the EEZ regime within the Convention does not address the specific individual and regional needs of states that have resulted in the wide discrepancy among state claims.